Penegakan Hukum Tindak Pidana Narkotika di Kalangan Mahasiswa Pada Wilayah Hukum Polrestabes Medan - Dimas B. Samuel Simanjuntak; Syafruddin Kalo; Mahmud Mulyadi; Sutiarnoto Sutiarnoto (Universitas Sumatera Utara, 2019)
Abstract : The rise of narcotics abuse cases is not only in big cities, but has reached small cities throughout the territory of the Republic of Indonesia ranging from lower middle socioeconomic level to upper middle socioeconomic level. According to the National Narcotics Agency (BNN), there are 5.1 million drug users in Indonesia, and that number is the largest in Asia. Of this amount, 40% of them came from among students. Based on data according to the employment status of drug suspects from 2015 to March 2019 in the jurisdiction of Medan Polrestabes obtained from the Medan Polrestabes Narcotics Unit globally (overall), because this study discusses narcotic crime among students, so this research is not widened to perpetrators from other job status. The data needed is a focus on narcotics offenders from among students only. Associated with data from Table 1 above, there are 123 narcotics crimes among students as many as 123 (one hundred and twenty three) students for a span of 5 (five) years in the Medan Regional Police jurisdiction. This shows that this research is important to do because students are the future of the nation. However, due to several factors causing him to fall into narcotics crime. Keywords : Narcotics crime; among students; the jurisdiction of Medan Polrestabes.